Food and pandemic. From nutritional misery to a new philosophy of food - Espinosa Bermejo, José Luis; Martínez Domínguez, Beatriz (Acta Sociológica, 2021)
The mexican federal government has indicated that the high number of infections and deaths from covid-19 is due to the fact that many of them suffer from one or more chronic diseases that are related to the consumption of ultra-processed foods, thus hindering their recovery. The purpose in this article is to analyze the actions of the Mexican federal government to promote changes in the diet of the population in order to achieve a healthier society. Among the manifest changes is the modification to the General Health Law to impose a new labeling on ultra-processed foods and avoid misleading advertising. It has also been achieved that in states such as Oaxaca and Tabasco the distribution, sale, gift and supply of sugary drinks and junk foods to minors is prohibited. On the other hand, the actions taken by the aforementioned food industry against government decisions on food matters are analyzed. Finally, it provides some urgent tasks that the federal government must undertake to strengthen the new food system and not be weakened by the powerful industrialized food producing industries.